Recuperación urbana y paisajística de la Carrera Tercera entre Calle 10 y 19 y el Parque Andrés López de Galarza en el centro fundacional. Ibagué. (2021)
This thesis project performs the urban analysis of the founding center of Ibagué Tolima, Colombia. Which takes into account the importance of generating a system of public space that articulates the urban environment and the social life in the city. Playing a landscape role that affects the feeling of well-being in the daily use of these routes. Likewise, give an urban and landscape recovery of the “third avenue” between 10th and 19th streets and the Andrés López de Galarza Park, in the founding center of Ibagué; within a problem of urban disconnection and deterioration of public space, to provide a proposal that performs a real synchronization with the urban needs of its inhabitants and visitors, increasing the development potential of the territory and improving the quality of urban life in the city